Meningkatkan Kemampuan Berbahasa Anak Melalui Metode Bercerita - Citra Prasiska Puspita Tohamba; Ukbayana Ukbayana (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Background: In PAUD programs, learning activities are designed to develop various aspects of child development, including language skills. Objective: This study aims to improve children's language skills through the application of the Storytelling Method in Group B of Ummul Mu'min Kindergarten, North Kolaka Regency. Methods: The study used a classroom action research design (PTK) with two cycles. The research subjects consisted of 16 children in Group B of Ummul Mu'min Kindergarten. Data were collected through observation, as well as documentation of the learning process. Results: The results showed that the implementation of the Storytelling Method significantly improved children's language skills. In cycle I, there was an increase from 40% to 72.22%, and in cycle II it reached a success rate of 93.75%. Conclusion: The implication of this study is that the Storytelling Method can be used as an effective alternative method in developing children's language skills at the kindergarten level. This research is expected to contribute to the development of learning strategies in kindergarten and provide guidance for teachers to design learning activities that support children's language development.